PENERAPAN ANALISIS FUNDAMENTAL TERHADAP PERUSAHAAN PERTAMBANGAN TBK DALAM MEMBELI SAHAM - YETTI AFRIDA INDRA (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2019)
The purpose of this research is to find out the influence Fundamental analysis ( of price earning ratio, earning per share, dividend per share, and dividend payout ratio) to the enhancement of mining companies’ stock price in 2014 – 2018 periods. The sample collection technique has been done by using purposive sampling method, and the samples are 6 companies. The statistic test method has been done by using multiple linier regression analysis. The independent variables in this research are price earning ratio, earning per share, dividend per share, and dividend payout ratio. The dependent variable is stock price. The result of this research show that price earning ratio, earning per share, dividend per share have significant and positive influence to the stock price. Meanwhile, dividend payout ratio have significant and negative influence to the stock price. It can be seen from the result of partial coefficient determination and it can be concluded that the variable which has dominant influence to the stock price is dividend per share because its partial coefficient determination is bigger than other independent variables.